(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The contribution presents some critical observations in order to the claim to recognize the “rule” of the autonomy and, consequently, of the law in order a sustain an analysis about L. 40/2004. Highlighting the vagueness of the notion of “sovereignty” and its crisis, the Author recovers some paradigms of juridical and political theory to recognize a renewed importance of the classical thought. The contribution makes an attempt to analyze the state crisis with the aim of recognizing the roots of this crisis, especially in verifying the failure to respect the “autonomy” as the origin of the rule of law.